Dykes, Sills, Laccoliths, and Inclined SheetsInclined Sheets Iceland in Iceland - Gudmundsson A.; Pasquare F. A.; Tibaldi A. (Springer, 2018)
DykeDykes and inclined sheets are extremely common in the volcanic systems of Iceland, both the fossil ones as well as the active systems. Until recently, comparatively few sills and laccoliths were known, but recent studies show that many laccoliths occur in the lava pile and that sills are also very common. Many, perhaps most, shallow magma chambers in Iceland (including laccoliths) develop from sillsSillformationgeometry, so that understanding the conditions for sill formation is of great volcanotectonic importance. Some of the laccoliths described here are felsic, others are mafic, and reach a maximum thickness of several hundred metres. They were emplaced at shallow depths (several hundred metres below the surface) and presumably acted as short-lived shallow magma chambers. Most sills in Iceland are mafic. The largest sills reach at least 120m in thickness and presumably many kilometres in diameter. Inclined sheets and vertical dykes supply magma to essentially all eruptions in Iceland. Sheet swarmsDyke swarm are confined to central volcanoes (stratovolcanoStratovolcanoes, calderaCalderas), whereas regional dykes occur outside central volcanoes. Most inclined sheet are injected from shallow magma chambers. Individual swarms of inclined sheets are circular to slightly elliptical in plan view (with a maximum diameter of about 18km), contain up to tens of thousands of sheets, generating a crustal dilation of as much as 80% (measured in a profile roughly perpendicular to the average sheet attitude), the sheets being mostly <1m thick and dipping 30°–60o towards the shallow magma source chamber. By contrast, the regional dyke swarms are highly elongated (elliptical) in plan view (with common maximum lengths of 50km and widths of 5–10km), contain hundreds of dykes at the level of exposure, mostly subvertical and 2–6m thick. Recent studies suggest that many regional dykes were emplaced through inclined or vertical magma flow. We conclude that, while much progress has been made, we still do not have reliable ...